Nasopharynx microflora features and its role in the spread of nosocomial infection - Krulyk, Nazarii; Halabitska, Iryna (Journal of Education, Health and Sport, 2022)
Introduction. The threat of the spread of nosocomial infection is exacerbated by a number of factors, among which we should note the increase in the number of multidisciplinary medical institutions of various forms of ownership, the creation of new types of medical instruments, devices, medical drugs, the introduction of new kinds of invasive (instrumental) diagnostic and therapeutic interventions, the increase in the number of patients with suppressed immunity (premature newborns, patients with chronic diseases of various origins, elderly people). The source of nosocomial infection can be patients, medical personnel, visitors, and objects of the hospital environment: tools, linen, furniture, air, and food. The main ways of transmission of nosocomial infections are aerosol (air-droplet, air-dust), contact (through tools, linen, furniture), parenteral (when administering drugs), fecal-oral (dirty hands), alimentary (through food). Aim: to investigate the microflora of the nasopharynx of visitors to medical and preventive care institutions, to reveal the prevalence of carriers of pathogenic strains. The role of visitors to hospital patients in the spread of nosocomial infections is an extremely relevant topic, as it is insufficiently studied and requires in-depth research. Materials and methods. 40 visitors to medical and preventive care institutions (MPCI) who had no signs of respiratory tract diseases and exacerbations of comorbid pathologies were examined. All the studied visitors of MPCI patients were divided into 3 age groups according to WHO recommendations: 1st group (n=15) – young patients (18-44 years old); 2nd group (n=14) – middle-aged patients (44-60 years old); The 3rd group (n=11) – elderly patients (60-75 years old). Compliance of the distribution of clinical trial data with the law of normal distribution was checked using the Shapiro–Wilk test. Arithmetic means to value and standard error (M±m) were used to describe the data. The concentration of bacteria in the sample was presented as a decimal logarithm. The results. Bacteriogram indicators of the mucous membrane of the back wall of the nasopharynx were analyzed in visitors to the MPCI patients in different age groups. Statistically significant differences were found in the concentration of representatives of the studied bacteriogram (p˂0.05), which indicates the influence of age on the composition of the microflora of the mucous membrane of the back wall of the nasopharynx A statistically significant difference was established in the concentration and composition of representatives of the bacteriogram of the mucous membrane of the back wall of the nasopharynx in visitors to the MPCI patients of different age groups (p˂0.05), which indicates the dependence of the composition of the microflora of the nasopharynx on age. A statistically significantly higher concentration of Staphylococcus aureus was found in the group of young patients (p˂0.05), which indicates the release of the most significant amount of this pathogen from the carriers of this group and an increase in the probability of developing infectious complications when in contact with visitors to the hospital, who were included in the added group, in comparison with other studied groups. Conclusion. Asymptomatic carriers of pathogenic strains of bacteria were found in all studied age groups of visitors to the hospital, which suggests the possibility that the studied patients may be a potential source of hospital infection in hospital patients, but this requires further research.